Students' achievement emotions in university courses – does the teaching approach matter?. Issue 10 (3rd October 2019) - Jacob, Barbara; Hofmann, Florian; Stephan, Melanie; Fuchs, Katharina; Markus, Stefan; Gläser-Zikuda, Michaela
ABSTRACT: Students' achievement emotions have an impact on learning and academic success. Therefore research on learning and teaching in higher education should not only focus on cognitive outcomes but on students' emotions, as well. The aim of our quasi-experimental study was to analyze students' achievement emotions based on the control-value approach in different instructional settings. An intervention was carried out with two teachers and 217 students referring to self-determination theory. We tested the influence of a student-oriented versus a teacher-centered approach on students' experience of self-determination and their achievement emotions. The results show a generally high level of students' positive achievement emotions. As expected, more autonomy and participation are experienced in student-oriented settings, but not more positive and less negative emotions than in teacher-centered settings. Main quantitative results are being discussed in terms of theoretical and methodological implications.